Efficiency of Australian technical and further education providers. (2nd January 2016) - Fieger, Peter; Villano, Renato; Cooksey, Ray
Abstract : Budgetary constraints on the public purse have led Australian Federal and State governments to focus increasingly on the efficiency of public institutions, including Technical and Further Education (TAFE) institutes. In this study, we define efficiency as the relationship between financial and administrative inputs and educational outputs. We employ stochastic frontier analysis in determining the efficiency of Australian TAFE institutes using data sourced from institutional annual reports, the Student Outcomes Survey and administrative databases. We found significant economies of scale effects and conclude that increasing institutional size for very small institutions may result in increased efficiencies.